Analisis Strategi Komunikasi Brand Identity Hotel AP Premier Dalam Meningkatkan Brand Awareness kepada Khalayak Kota Batam - Leong, Glenn Stevander Glenn Jeremiah; Rorong, Michael Jibrael (SCIENTIA JOURNAL, 2024)
This research focuses on the transformation of Travelodge into AP Premier Hotel, a new city hotel brand, which emphasises the importance of a well-conceived communication strategy for brand development. Using various data collection techniques, including interviews, documentation review, and observation, this research highlights the critical role of communication strategy in shaping the brand identity of AP Premier Hotel Batam. The findings underline that effective communication patterns are essential to build brand awareness and a positive image for AP Premier. The research concludes that the communication strategies used are aligned with the principles of marketing and branding, inspired by Jean-Noël Kapferer's theory. The emphasis on service excellence in communication activities resulted in three different patterns: linear, interactional, and transactional. Through these patterns, this research shows the cultivation of brand awareness and a good brand image for the AP Premier brand.